The Extraordinary Solution for Indonesia Economic Crisis: Shariah Capital Market - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
l11e historical development of the Islamic finance industry which includes banking, insurance and capital markets is fundamentilly a very long historical process. l11e Islamic Shari.a principles applied in the banking industry and Cairo is a country founded the first Islamic bank around 1971 under the name "Nasser Social Bank" operations based on a revenue sharing system (without usury). Islamic principles in mua1JJi:ilah that must be considered by the perpetrators of Islamic investment (related parties) are: 1.Do not look for profit in things forbidden, both in terms of substance and how to get it, and do not use it for things that are forbidden. 2. No oppressing and oppressed 3.Justice distribution of prosperity. 3. Transactions carried out on basis of the same pleasure. No element of riba, mqysir and gharar (vagueness). No doubt, to see the development of the Islamic capital market industry is still new. The effect of conventional economic outlook i still strongly felt.